THE ECONOMIC AND SOCIAL JUSTIFICATIONS FOR PUBLIC SPENDING TO AGRICULTURE : THEORETICAL INSIGHTS AND EMPIRICAL OBSERVATIONS - Aldona Zawojska (Acta Scientiarum Polonorum. Oeconomia, 2013)
This paper explores the theoretical justifi cations for public expenditures to support the agriculture sector and farming population. The market failure and welfare rationale for government intervention is contrasted with government failures. In addition to the normative analysis, the paper presents empirical evidence on the level of public agricultural expenditure based on cross-country data with main focus on the European Union countries. The results of own cross-country statistical analysis suggest that per capita costs of EU support to agriculture are only weakly related to the general economic development of the individual countries but this support is relatively more important for the economies of less developed EU members. A look at the findings of the reviewed country studies exploring the link between public expenditure allocated to agriculture and the sector performance reveals that this way to support farming and rural economy may be effective, exerting a positive effect on growth in crop and livestock production, private-sector investments in agriculture and rural and general poverty reduction, but its impact depends on the type of expenditure.